Electromagnetic pulse reduces free radical generation in rat liver mitochondria in vitro. (April 2013) - Wang, C.; Zhou, H.; Peng, R.; Wang, L.; Su, Z.; Chen, P.; Wang, S.; Wang, S.; Liu, Y.; Cong, J.; Wu, K.; Hu, X.; et al.
Abstract Non-ionizing radiation electromagnetic pulse (EMP) is generally recorded to induce the generation of free radicals in vivo. Though mitochondria are the primary site to produce free radicals, a rare report is designed to directly investigate the EMP effects on free radical generation at mitochondrial level. Thus the present work was designed to study how EMP induces free radical generation in rat liver mitochondria in vitro using electron paramagnetic resonance technique. Surprisingly, our data suggest that EMP prevents free radical generation by activating antioxidant enzyme activity and reducing oxygen consumption and therefore free radical generation. Electron spin resonance measurements clearly demonstrate that disordering of mitochondrial lipid fluidity and membrane proteins mobility are the underlying contributors to this decreased oxygen consumption. Therefore, our results suggest that EMP might hold the potentiality to be developed as a non-invasive means to benefit certain diseases.